2014
DOI: 10.21608/besps.2014.34798
|View full text |Cite
|
Sign up to set email alerts
|

Effect Of L-Citrulline And Ranitidine On Indomethacin-Induced Gastric Ulcer In Male Albino Wister Rats

Abstract: Aim: to investigate the effect of L-citrulline and ranitidine (RAN) on indomethacin-induced gastric ulcer in male albino Wister rats. Methods: 50 male albino Wister rats were divided into 5 groups (10rats each): control received normal saline, indomethacin (IND) group; in which gastric ulceration was induced by a single dose of IND (30mg/kg) intragastrically, IND+RAN group; pretreated with RAN (50mg/kg) intragastrically, IND+ L-citrulline group; pretreated with Lcitrulline (900mg/kg) intragastrically, IND+RAN+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Although its pathogenesis has yet been elucidated, it is considered a consequence of the overburdened resistance and downgraded self-repair capability of the gastric mucosa after damages [1][2][3]. Current Western medicine treatment for gastric ulcers mainly employs drugs that inhibit gastric acid and protect the gastric mucosa and anti-Hp drugs which alleviate the clinical symptoms of patients but also lead to obvious side effects, resulting in a predisposition to more serious diseases [4,5]. Moreover, clinical studies have shown that Western medicine treatment fails to optimize the quality of ulcer healing (QOUH), with the recurrence rate reaching 80% 1 year after drug withdrawal [6,7], which is indicative of an unsatisfactory overall efficacy.…”
Section: Introductionmentioning
confidence: 99%
“…Although its pathogenesis has yet been elucidated, it is considered a consequence of the overburdened resistance and downgraded self-repair capability of the gastric mucosa after damages [1][2][3]. Current Western medicine treatment for gastric ulcers mainly employs drugs that inhibit gastric acid and protect the gastric mucosa and anti-Hp drugs which alleviate the clinical symptoms of patients but also lead to obvious side effects, resulting in a predisposition to more serious diseases [4,5]. Moreover, clinical studies have shown that Western medicine treatment fails to optimize the quality of ulcer healing (QOUH), with the recurrence rate reaching 80% 1 year after drug withdrawal [6,7], which is indicative of an unsatisfactory overall efficacy.…”
Section: Introductionmentioning
confidence: 99%